EARLY CHRISTIAN MISSIONARIES AND WOMEN EDUCATION IN CROSS RIVER STATE, NIGERIA: A MODEL FOR THE CHURCH TODAY - Nzeyo Gabriel Eteng (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The paper titled: Early Christian Missionaries and Women Education in Cross River State, Nigeria: A Model for the Church Today, is motivated by the quest to explore the impact of the early Christian missionaries' activities in Cross River State. Most scholars think that Christianity was used as a tool of British imperialism. Before the advent of Christianity in Cross River State, women were backward and associated with various taboos, they were regarded as people who lacked the potential useful for development other than child-bearing and rearing. The early Christian missionaries introduced Western Education in Calabar as early as 1846. Initially, the missionaries encountered difficulties in convincing parents to send their daughters to school, but they succeeded in convincing parents to support the girl-child education with much persuasion. The research is anchored on two theories, the relational feminist theory propounded by Carol Gilligan and the liberal feminist theory propounded by Mary Walstone Craft. It adopts the historical and descriptive method of data collection and the qualitative method of analysis. Women benefited from western education and began to make significant strides in different careers of their choices. Through the instrument of conscientization, the church should educate women to stand the challenges of global health and insecurity in Nigeria.